1999
DOI: 10.1074/jbc.274.19.12979
|View full text |Cite
|
Sign up to set email alerts
|

SEC14-dependent Secretion inSaccharomyces cerevisiae

Abstract: The SEC14 gene in Saccharomyces cerevisiae encodes a phosphatidylinositol transfer protein required for secretory protein movement from the Golgi. Mutation of SAC1, a gene of unknown function, restores secretory flow in sec14-1 ts strains. The existing model for the bypass of the sec14-1 ts defect by sac1-22 involves stimulation of sphingolipid biosynthesis and, in particular, the synthesis of mannosyl-diinositolphosphoryl-ceramide with concomitant increases in Golgi diacylglycerol levels. To test this model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 30 publications
3
21
1
Order By: Relevance
“…6). DISCUSSION We recently demonstrated that a mutation, sac1-22, that suppresses the growth and secretion defect of sec14-3 mutants causes a specific and pronounced elevation in the cellular level of PtdIns(4)P (19). It was also demonstrated by others that SAC1 encodes a novel multifunctional phosphoinositide phosphatase that can use PtdIns(4)P, among other phosphoinositides, as a substrate (20).…”
Section: Delivery Of Cpy To the Vacuole Is Not Blocked In Pik1 Tsmentioning
confidence: 82%
See 3 more Smart Citations
“…6). DISCUSSION We recently demonstrated that a mutation, sac1-22, that suppresses the growth and secretion defect of sec14-3 mutants causes a specific and pronounced elevation in the cellular level of PtdIns(4)P (19). It was also demonstrated by others that SAC1 encodes a novel multifunctional phosphoinositide phosphatase that can use PtdIns(4)P, among other phosphoinositides, as a substrate (20).…”
Section: Delivery Of Cpy To the Vacuole Is Not Blocked In Pik1 Tsmentioning
confidence: 82%
“…When cultures reached midexponential phase (A 600 nm ϭ ϳ0.8), one-half of each culture was shifted to 37°C for 1 h prior to termination of growth by addition of trichloroacetic acid (5% final concentration). Extraction of lipids and their analysis by high pressure liquid chromatography (HPLC) were carried out as described in detail previously (19,37).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of bypass mutants has led to the suggestion that Sec14p is required for maintenance of a critical pool of diacylglycerol [21,22]. Moreover, Sec14p can also fa-cilitate PtdIns4P production in i o [22,23] ; this lipid might also be a critical requirement in protein secretion. In another yeast, Yarrowia lipolytica, SEC14 is not an essential gene and is required only for differentiation from yeast to a mycelial growth form [24].…”
Section: Introductionmentioning
confidence: 99%